Is L(x) a Linear Transformation from R3 to R2?

In summary, we are given a transformation L(x) = (1 + x1, x2) and we are asked to determine if it is a linear transformation from R3 to R2. To do this, we must check if it satisfies the defining properties of a linear transformation, which are L(x + y) = L(x) + L(y) and L(cx) = cL(x). In the attempt at a solution, the conversation shows a misunderstanding of how to check for linearity. The writers use examples that do not properly use the given transformation, leading to incorrect conclusions. For example, L(2x) is not equal to 2L(x), but rather L(2x) = 2L
  • #1
Dustinsfl
2,281
5

Homework Statement


Determine if this is a linear transformation from R3 to R2


Homework Equations


L(x) = (1 + x1, x2)


The Attempt at a Solution


Whenever I perform addition and scalar multiplication, I obtain this is closed under both. The book says this isn't a transformation though.
 
Physics news on Phys.org
  • #2
Dustinsfl said:
Determine if this is a linear transformation from R3 to R2

L(x) = (1 + x1, x2)

Hi Dustinsfl! :smile:

Is L(2x) = 2L(x) ? :wink:
 
  • #3
I don't see how that doesn't work.

(2 + 2*x1, 2*x2) = 2*(1 + x1, x2)
 
  • #4
Dustinsfl said:
I don't see how that doesn't work.

(2 + 2*x1, 2*x2) = 2*(1 + x1, x2)

No, L(2x) = L((2x1,2x2,2x3)) = (1 + 2x1,2x2)
 
  • #5
Based on that then, the other problems the book says are transformations would fail then too.
 
  • #6
Here is a similar problem which is a transformation:
L(x)= (x2, x3)

Since there is no x1, this one would also fail on that premise but the book states this one is a transformation.
 
  • #7
I think you are missing something. To show that a transformation L is linear, show that L(x + y) = L(x) + L(y), and that L(cx) = cL(x).

For L(x) = (x2, x3), where x = (x1, x2, x3),

L(x + y) = L(x1 + y1, x2 + y2, x3 + y3) = ( x2 + y2, x3 + y3) = (x2, x3) + (y2, y3) = L(x) + L(y)

L(cx) = L(cx1, cx2, cx3) = (cx2, cx3) = c(x2, x3) = cL(x).

Therefore, L is a linear transformation.
 
  • #8
Mark44 said:
For L(x) = (x2, x3), where x = (x1, x2, x3)

So looking at a 2 dimension example, this still doesn't make any sense. You are saying x=(x1, x2).

If L(x) = (-x1, x2), then verifying scalar multiplication we would obtain (cx1, cx2)=c(x1, x2) which doesn't equal c*L(x).

The problem with this conclusion is that this example I just did is a linear transformation and is closed under addition and multiplication.
 
  • #9
Dustinsfl said:
So looking at a 2 dimension example, this still doesn't make any sense. You are saying x=(x1, x2).
No, I'm not. I specifically said for that problem, that x = (x1, x2, x3).
Dustinsfl said:
If L(x) = (-x1, x2), then verifying scalar multiplication we would obtain (cx1, cx2)=c(x1, x2) which doesn't equal c*L(x).
You're leaving out some pretty important stuff, and are arriving at incorrect conclusions. The whole story for this new problem is
L(cx) = L(cx1, cx2) = (-cx1, cx2) = c(-x1, x2) = cL(x).
Dustinsfl said:
The problem with this conclusion is that this example I just did is a linear transformation and is closed under addition and multiplication.
The problem with your conclusiong was that it was wrong. Do you see now why it was wrong?
 
  • #10
So if that is the case,looking at my original post transformation, then how is it not a linear transformation?
 
  • #11
Work it through, following my work as a template. For that transformation, and using tiny-tim's hint, what is L(2x)? Is L(2x) = 2L(x)?
 
  • #12
Here is where both of your explanations are esoteric. We are saying x=(x1,...,xn).

Next, we are using x times the scalar and then comparing that with L(x). Unless we plug in L(x) or x is equal to L(x), it will never be closed. Hence, I used the this as my example to show that:

"So looking at a 2 dimension example, this still doesn't make any sense. You are saying x=(x1, x2).

If L(x) = (-x1, x2), then verifying scalar multiplication we would obtain (cx1, cx2)=c(x1, x2) which doesn't equal c*L(x).

The problem with this conclusion is that this example I just did is a linear transformation and is closed under addition and multiplication."

Now looking at what you said next you are using L(x) not x.
"You're leaving out some pretty important stuff, and are arriving at incorrect conclusions. The whole story for this new problem is
L(cx) = L(cx1, cx2) = (-cx1, cx2) = c(-x1, x2) = cL(x)."

If we do they same with the original problem, it will be closed.
 
  • #13
Maybe you are confusing a vector x (note the use of bold) with its components, x1, x2, x3, ...

I can't tell what it is that you're not getting, but something is not clicking.

Dustinsfl said:
If L(x) = (-x1, x2), then verifying scalar multiplication we would obtain (cx1, cx2)=c(x1, x2) which doesn't equal c*L(x).
You didn't use L here. The equation (cx1, cx2)=c(x1, x2) is true for any vector in R2, due to the vector space properties of scalar multiplication.

Most of what you said in your last reply I don't understand. Instead of me trying to understand what you meant, see if you can work through what I asked you to do, using the transformation in your first post.

Here, x = (x1, x2, x3), and L(x) = (1 + x1, x2)

L(2x) = ?
 
  • #14
I understand what you are saying but the way we addressing this problem makes this one not closed then too.

x=(x1, x2) and L(x)=(-x1, x2)

L(2*x)=(2*x1, 2*x2)

Which doesn't equal L(x) when 2 is factored since x1 is positive.
 
  • #15
Dustinsfl said:
I understand what you are saying but the way we addressing this problem makes this one not closed then too.

x=(x1, x2) and L(x)=(-x1, x2)

L(2*x)=(2*x1, 2*x2)

Which doesn't equal L(x) when 2 is factored since x1 is positive.
Again, you are not using the transformation. This is what you should have.

L(2*x) = L(2*x1, 2*x2) = (-2x1, 2x2) = 2(-x1, x2) = 2L(x).

It's a simple matter to show that this works for any scalar c.

L(c*x) = L(c*x1, c*x2) = (-cx1, cx2) = c(-x1, x2) = cL(x).

So this transformation is closed under scalar addition.

Now work the one that tiny-tim and I have been asking you to work.
 
  • #16
L(cx)=(cx1, cx2, cx3)=(c(1+x1), cx2)=c(1+x1, x2)=cL(x)

If it isn't suppose to be closed, I don't know how working this one was suppose to verify that.
 
  • #17
This problem has nothing to do with closure. It's just asking you to check if the transformations satisfy the defining properties of a linear transformation.

You're making some really basic math errors. This is just scalar multiplication of a vector:

cX=(cx1,cx2,cx3)

It has nothing to do with L. This is just substitution:

L(cX)=L(cx1,cx2,cx3)

Now use the definition of L to write down what L(cx1,cx2,cx3) is equal to:

L(cx1,cx2,cx3)=(1+cx1,cx2)

Do you see how this is different from what you've written above?
 
  • #18
Dustinsfl said:
L(cx)=(cx1, cx2, cx3)=(c(1+x1), cx2)=c(1+x1, x2)=cL(x)

If it isn't suppose to be closed, I don't know how working this one was suppose to verify that.
Here's your problem:
L(cx)=(cx1, cx2, cx3) [itex]\neq[/itex] (c(1+x1), cx2).

What does L in this transformation do to an input vector? It adds 1 to the first component, keeps the second component, and discards the third component.

Here's what you should have:
L(cx)=(cx1, cx2, cx3)= (1 + cx1, cx2)

Can you still assert that L(cx) = cL(x)?
 
  • #19
(Mark44 :smile: seems to go to bed slightly later than i do! :zzz:)
Dustinsfl said:
L(cx)=(cx1, cx2, cx3)=(c(1+x1), cx2)=c(1+x1, x2)=cL(x)

No!

L(cx) is not equal to (cx1, cx2, cx3) …

it is equal to L(cx1, cx2, cx3).

And then L(cx1, cx2, cx3) is not equal to (c(1+x1), cx2) …

it is equal to (1 + cx1, cx2).

You see? :smile:
 

1. What is a transformation from R3 to R2?

A transformation from R3 to R2 is a mathematical function that maps a point in three-dimensional space to a point in two-dimensional space. It can be represented by a 2x3 matrix and can be used to represent physical processes such as rotation, translation, and scaling.

2. How is a transformation from R3 to R2 represented?

A transformation from R3 to R2 can be represented by a 2x3 matrix, where each row represents a coordinate in the two-dimensional space and each column represents a coordinate in the three-dimensional space. The values in the matrix determine the specific transformation being performed.

3. What is the purpose of a transformation from R3 to R2?

The purpose of a transformation from R3 to R2 is to simplify and represent complex physical processes or data in a more manageable and understandable way. It allows for easier visualization and analysis of data in two-dimensional space, while still preserving important information from the original three-dimensional space.

4. What are some common applications of transformations from R3 to R2?

Transformations from R3 to R2 are commonly used in computer graphics, engineering, and physics. They are also used in data analysis and visualization to reduce the dimensionality of data and make it easier to interpret and analyze.

5. How do you perform a transformation from R3 to R2?

To perform a transformation from R3 to R2, you multiply the coordinates of a point in three-dimensional space by a 2x3 transformation matrix. The resulting coordinates will be the point's location in two-dimensional space after the transformation has been applied.

Similar threads

  • Calculus and Beyond Homework Help
Replies
4
Views
2K
  • Calculus and Beyond Homework Help
Replies
26
Views
2K
  • Calculus and Beyond Homework Help
Replies
5
Views
1K
  • Linear and Abstract Algebra
Replies
1
Views
861
  • Calculus and Beyond Homework Help
Replies
2
Views
778
  • Calculus and Beyond Homework Help
Replies
2
Views
1K
  • Calculus and Beyond Homework Help
Replies
12
Views
961
  • Calculus and Beyond Homework Help
Replies
5
Views
1K
  • Calculus and Beyond Homework Help
Replies
9
Views
1K
  • Calculus and Beyond Homework Help
Replies
18
Views
5K
Back
Top